Risk factors associated with abandonment of care in retinoblastoma: analysis of 692 patients from 10 countries - Nishath, T (2023)
Background Rates of care abandonment for retinoblastoma (RB) demonstrate significant geographical variation; however, other variables that place a patient at risk of abandoning care remain unclear. This study aims to identify the risk factors for care abandonment across a multinational set of patients. Methods A prospective, observational study of 692 patients from 11 RB centres in 10 countries was conducted from 1 January 2019 to 31 December 2019. Multivariate logistic regression was used to identify risk factors associated with higher rates of care abandonment. Results Logistic regression showed a higher risk of abandoning care based on country (high-risk countries include Bangladesh (OR=18.1), Pakistan (OR=45.5) and Peru (OR=9.23), p<0.001), female sex (OR=2.39, p=0.013) and advanced clinical stage (OR=4.22, p<0.001). Enucleation as primary treatment was not associated with a higher risk of care abandonment (OR=0.59, p=0.206). Conclusion Country, advanced disease and female sex were all associated with higher rates of abandonment. In this analysis, enucleation as the primary treatment was not associated with abandonment. Further research investigating cultural barriers can enable the building of targeted retention strategies unique to each country. © Author(s) (or their employer(s)) 2023.